O estudante de gerontologia e a sua percepção frente à complexidade vida/morte e morte/vida - Cardozo, Carlos Eduardo Santos (2021)
This thesis addresses a challenging and current theme: education for death in the training of gerontologists. Educating for death is the process of training and preparing people to deal with coping at the end of life. Learning about the last stage of human development is a fundamental role for professionals specialized in gerontology, in supporting the elderly in the aging process and in cases of palliative care. The object contemplated was the gerontology student and their perception of the complexity of life/death and death/life. With the research, which resulted in this thesis, we sought to answer the following questions: Is the reflection on finitude and death a relevant theme for future specialists in the field of Gerontology? Is it an integrative topic in your professional training? Do courses offer a subject academic that examines issues related to death? The methodology used was the qualitative approach research used in the focused interview, to know and understand the importance of the study on finitude and death. The theoretical framework used was based on the complex thought proposed by Edgar Morin, particularly the operators of complexity and imaginary complexes. The interviews were conducted with six students specializing in gerontology, graduated in different areas of knowledge; two are Physical Education professionals; two from Nursing; one from Physiotherapy and one from Dentistry. The themes considered for the analyzes were only to sectorize the interviews, since, dealing with the subjectivity of the participants, they are not exhausted in themselves. Some pointed out that the issue of finitude and death are not integrating subjects in their training and this discussion was missing, which was often dealt with quickly or even not presented. In view of this, gerontology, in addition to presenting protocol intervention techniques, could produce reflection on death in the final stage of life. Advancing from academic training to and with human training is a challenge for specialization courses in gerontology. Finally, the considerations of the author of this thesis presented only one possible look, it is an invitation for the reader to find their own impressions.